PEMBERIAN KOMPRES HANGAT DAN KOMPRES ALKOHOL SEBAGAI ALTERNATIF INTERVENSI KEPERAWATAN FLEBITIS PADA PASIEN YANG TERPASANG INFUS - IRIENE KUSUMA WARDHANI, - (2006)
"Phlebitis is a common problem in infused patient. It may result from several factor, chemical, mechanical, and bacterial. Today, nursing intervention for phlebitis remainds debatable. The objective of this study was to analyze the effectiveness ofwarm and alcohol compress in reducing phlebitis. This study was a quasi experiment study. The population was phlebitis patient treated at Surgical Wards, Dr. Soetomo Hospital, Surabaya. Total sample consisted of 14 persons. The dependent variable was phlebitis, and the independent variables were warm compress and alcohol compress. Data were collected using direct observation to the respondent. Collected data were subjected to statistical test using Wilcoxon Signed Rank test and Mann Whitney U test. The result showed that warm compress and alcohol compress had similar significance value (p = 0,027), which was lower than alpha = 0,05, indicating the influence of warm and alcohol compress to the reduction of phlebitis. In conclusion, the use of warm and alcohol compress is effective to reduce phlebitis in infused patient. As it's proved that the use of warm and alcohol compress had no difference quantitatively, there should be a promotion to use this alternative as a nursing intervention for phlebitis treatment."